Multiple use forestry planning: Timber and Brazil nut management in the community forests of Northern Bolivia - Cronkleton, P.; Guariguata, Manuel R.; Albornoz, M.A. (2011)
In Bolivia’s Northern Amazon, forests long used for the extraction of non-timber forest products (NTFPs) are now experiencing increased logging. The extraction of timber and economically important NTFPs such as Brazil nuts (from the emergent forest tree Bertholletia excelsa) is occurring in the same forests and provides a clear opportunity to integrate management decisions and planning. Bolivia’s forestry legislation allows, in principle, the management of multiple forest resources. However, there is little evidence that the opportunity has led to greater integration of management decisions and practice. Actually, management of each resource is typically carried out by different stakeholders with resident families responsible for Brazil nut gathering while logging companies carry out the timber harvest. This paper analyzes community forest management plans in Northern Bolivia to examine whether community residents participated in the development and implementation of the timber management plans, and the extent to which proponents of timber management plans attempted to integrate Brazil nut management into timber harvesting. The research draws on analysis of approved timber management plans for community forests and focus group interviews with residents in selected forest communities. Based on observations, the paper concludes that multiple-use management in these forests could be improved by strengthening community level institutions by confirming their authority over timber management operations and by building capacity to oversee and monitor the extraction activities of loggers working on their land.